(untitled) (Cambridge, UK, 2004)
This lively collection of over 100 classroom activities allows teachers to exploit the language learning potential of extensive reading. The activities were contributed by teachers who have used them successfully in classrooms all over the world, introduce extensive reading to students, and link it with the rest of the language curriculum. Here is a wealth of ideas for encouraging students to read, and for using students' reading experiences for further language practice and learning. These creative and enjoyable speaking, listening, role play, reading, writing, and vocabulary activities are suitable for students of all ages and levels. Each activity is clearly explained, together with a personal note from its author. This is a handbook for teachers of general language courses, or grammar, listening, speaking, writing, or reading courses. It is written for teachers both non-native and native speaking, and for teachers both novice and experienced. It will also be of interest to teacher-educators.
Keywords: Language and languages,Reading; Study and teaching